Pengembangan Aplikasi Dengan Metode Agile Untuk Pengolah Data Pinjaman Pada BRI Cabang Binjai - Farhan Aprian Tritama; Eko Hariyanto (JURNAL TEKNOLOGI DAN ILMU KOMPUTER PRIMA (JUTIKOMP), 2023)
Banks are business entities that collect funds from the public through savings and distribute them to the people through credit. BRI Binjai City branch, as one of the government banks, faces challenges in monitoring customer loan payments, also known as debtors. Information regarding the smooth status of debtor payments is still processed manually using computer tools. However, this is still considered ineffective because processing a large amount of debtor payment data takes time. Apart from that, the accuracy of the processing carried out by banking employees also influences the final results you want to know. This research aims to develop a web-based application for monitoring debtor loan payment status using agile methods and UML design. The results of the analysis of the design and implementation of this application make it easier for admins to process loan and payment data and obtain recapitulation reports on the smoothness of debtor payments.